Qualitative Real-Time PCR SYBR Green Detection of Petri Disease Fungi - Overton, B.E.; Stewart, E.L.; Qu, X.; Wenner, N.G.; Christ, B.J. (Phytopathologia Mediterranea, 2004)
Real-time PCR provides a fast, reliable, and cost-effective method for detecting the presence or absence ofPetri disease fungi in grapevines. The primer pairs, Pmo1f + Pmo2r, and Pac1f + Pac2r, were designed for species andgenus-specific amplification of Phaeomoniella chlamydospora and Phaeoacremonium spp. respectively, using realtimePCR with SYBR® Green. The primers were specific and showed no primer-primer dimers until after 35 cycles.Pa. chlamydospora was detected in roots, shoots, and young trunks of drill-inoculated vines. Phaeoacremonium wasdetected in trunk cross-sections of naturally infected vines from which Phaeoacremonium aleophilum had been isolated.The protocol presented here can be adapted to provide a reliable detection system for research and industry.